1992
DOI: 10.1007/bf02535863
|View full text |Cite
|
Sign up to set email alerts
|

Human milk in disease: Lipid Composition

Abstract: Differences in the lipid composition of human milk have been described in maternal diseases known to affect fat metabolism. Diseases such as diabetes, cystic fibrosis, hypobetalipoproteinemia and Type I hyperlipoproteinemia affect the quantity and quality of human milk fat. Increased fatty acid chain elongation and changes in desaturation (especially delta 6 desaturase), as well as changes in lipid class composition, have been shown in diabetes and cystic fibrosis, whereas compensatory increases in medium-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…Indeed, Hiltunen et al (1986) have demonstrated the retroconversion of 20:4n-6 to 14:2n-6 in rat liver peroxisomes. Likewise, 14:ln-9 must be derived from 18:ln-9 because the double bond in 14:l produced by de nouo synthesis is in the n-5 position [reviewed by Jensen et al (1990);Hamosh & Bitman, 1992;Kolezko & Springer, 19921. Since retroconversion is an active catabolic pathway in retina, it should be considered a potential source of these short-chain unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hiltunen et al (1986) have demonstrated the retroconversion of 20:4n-6 to 14:2n-6 in rat liver peroxisomes. Likewise, 14:ln-9 must be derived from 18:ln-9 because the double bond in 14:l produced by de nouo synthesis is in the n-5 position [reviewed by Jensen et al (1990);Hamosh & Bitman, 1992;Kolezko & Springer, 19921. Since retroconversion is an active catabolic pathway in retina, it should be considered a potential source of these short-chain unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariando a literatura [32][33][34] , neste trabalho foram obtidos maiores valores energéticos no colostro que no leite maduro (Tabela 2), embora os resultados possam ser considerados estatisticamente iguais em função do alto desvio padrão. Os lipídios são os componentes mais variáveis na composição do leite humano e sua quantidade pode variar em função do perío-do de lactação (colostro e maduro), do período da mamada (diurno ou noturno) e ao longo de cada mamada (leite do início e do fim) 5 .…”
Section: Composição Centesimalunclassified
“…We first tested whether 14:1n-9 and 14:2n-6 might be generated by de novo synthesis, because the 14:1n-5 isomer can be synthesized via a ⌬ 9 -desaturase (Hamosh and Bitman, 1992;Koletzko et al, 1992), but we found that 14:0 does not serve as a desaturase substrate in the retina and only 16:0 and 18:0 are produced. We next considered that 14:1n-9 and 14:2n-6 might be produced during the ␤-oxidation (retroconversion) of long chain unsaturated fatty acids.…”
Section: Distribution Of Desaturation Elongation or Retroconversionmentioning
confidence: 99%